Judicial Review of Administrative Regulations: Constitutional Justice vs Administrative Justice - Zarikyan, Karen (NAS RA)
The main purpose of the article is to discuss two forms of judicial control over administrative regulation (constitutional and administrative justice) and identify the problems related to the distribution of functions between them. The core of the research is the theoretical characterization of judicial review of administrative regulations and examination of Armenian practice. In particular, the article explains the essence and the features of administrative regulations and, on this basis, attempts to provide a scientifically grounded answer to the question of how their legality should be verified. As a result of the research, the author’s approach to the separation of the mechanisms of constitutional and administrative justice during judicial control over administrative regulations is presented. It is stated that the legality of administrative regulations can be verified within the framework of constitutional justice only in case the protection of human rights has not been ensured by the mechanisms of administrative one. This includes cases where legality of administrative regulations is discussed regarding their compliance with constitutional requirements.
Keywords: Legal Studies